CUSTOMER SATISFACTION TOWARD SAMBAL DCABEAN PRODUCT - Nadia Jayalianti; Reny Sukmawani; Neneng Kartika Rini (Proceeding of International Seminar on Agricultural Conservation and Cultural Heritage, 2025)
The culinary industry in Indonesia represents a strategic sector that fosters socio-economic development, propelled by the growing demand for practical and high-quality food products. This study aims to analyze consumer satisfaction regarding the Sambal Dcabean product produced by Koperasi Tani Mandiri Sejahtera in Sukaraja District, Sukabumi Regency. The research utilized a descriptive quantitative method and included 50 respondents selected through purposive sampling. Data were gathered by distributing online questionnaires via google forms. The results, analyzed using the Likert Scale, indicate that the consumer satisfaction index for Sambal Dcabean has reached 89%, suggesting that customers are highly satisfied with the product. Further analysis showed that customer satisfaction levels are signifinly high across three main variables : product quality (89.27%), price (87.60%), and service (89.47%). These findings underscore the significane of maintaining high product quality, adopting competitive pricing strategies, and enchancing service quality to cultivate customer loyalty and seize market opportunities